New synonyms, combinations and status in the Chinese species of the family Meloidae Gyllenhal, 1810 (Coleoptera: Tenebrionoidea) with additional faunistic records - Pan, Zhao; Ren, Guo-Dong (Zootaxa, 2020)
On the ground of the taxonomic revision of the family Meloidae Gyllenhal, 1810 from China and extensive examination of type specimens, the following new synonyms and combinations of blister beetle species are established: Zonitis bomiensis Tan, 1988 syn. nov. = Longizonitis semirubra (Pic, 1911); Schroetteria subpolita Reitter, 1911 syn. nov. = Megatrachelus politus (Gebler, 1832); Epicauta rishwani Makhan, 2013 syn. nov. = Denierella emmerichi Pic, 1934; Epicauta thailandica Dvořák, 1996 syn. nov. = Denierella venerabilis Kaszab, 1956; Epicauta mojiangensis Tan et Deng, 1993 syn. nov. = Epicauta makliniana Kaszab, 1958; Epicauta xantusi Kaszab, 1952 syn. nov. = Epicauta obscurocephala Reitter, 1905; Lytta badeni Haag-Rutenburg, 1880 syn. nov. = Epicauta sibirica (Pallas, 1773); Epicauta badeni sinica Kaszab, 1960 syn. nov. = Epicauta sibirica (Pallas, 1773); Lytta choui Wang, Wang et Ren, 2012 syn. nov. = Lytta suturella (Motschulsky, 1860); Zonabris calida var. baicalica Pic, 1919 syn. nov. = Mylabris aulica Ménétriés, 1832; Zonitomorpha kimi (Kôno, 1936) comb. nov.; Zonitomorpha miwai (Kôno, 1936) comb. nov.; Zonitoschema fuscimembris (Fairmaire, 1886) comb. nov. Furthermore, Zonitoschema macroxantha yunnana Kaszab, 1960 is provisionally raised to Z. yunnanum stat. nov. A lectotype is designated for Zonitoschema fuscimembris. Six new Chinese province records of five species (Denierella emmerichi, Epicauta obscurocephala, Epicauta sibirica, Lytta suturella, and Mylabris aulica) are reported. Illustrations are provided for 21 type specimens, the aedeagus of two Zonitoschema species, and the antennomere XI of two Mylabris species.